A Review of Alcohol-Related Harms: A Recent Update - Abedin Iranpour; Nouzar Nakhaee (Addiction and Health, 2019)
In the early decades of the 20th century, discussions regarding alcohol were dominantly directed toward itstherapeutic uses, but authorities now state that any level of alcohol consumption poses negative effects onhealth. Over recent months, increased attention has been devoted to disease burdens attributable to alcoholuse worldwide. As more and more studies are conducted to illuminate the harmful effects of alcohol ondifferent body systems, the mounting evidence generated requires documentation and publication. Thecurrent review was aimed at providing an overview of the recent literature on the adverse consequences ofalcohol consumption.